Features of the Clinical Course of Infective Endocarditis in Children - Oleksandr H. Senko (Український журнал серцево-судинної хірургії, 2025)
Infective endocarditis (IE) in children is less common than in adults but is associated with a significantly higher mortality rate. At the same time, diagnosis and treatment in young patients are complicated by a higher prevalence of congenital heart defects (CHD). We studied the spectrum of microorganisms and clinical manifestations in children.